BLENDED LEARNING AND THE MOST FREQUENTLY RESEARCHED OF COMPLEX ADAPTIVE BLENDED LEARNING SYSTEM - Salvida Yunita (Journal Informatic, Education and Management (JIEM), 2026)
This qualitative research aims to find out the most commonly Complex Adaptive Blended Learning Systems used in teaching English. Thus, 65 pieces of studies were analyzed by using tables and charts which are categorized based on the content of the research reports. Quantitative data from each item found in the research reports are reported in fourteen tables. The result of the data analysis shows that the higher frequency belongs to learning support which is 18 papers (27.69%) of total Blended Learning papers on English Language Teaching. Then, it follows by teachers which are 6 papers (9.23%). Then, it is followed by content which is 5 papers (7.69%) and learners which are 5 papers (7.69%), and technology which is 3 papers (4.61%). Meanwhile, the least amount of Blended Learning Subsystem papers is the institution which is only 1 paper (1.53%).  Finally, this study highlights the latest research trends from Blended Learning on English Language Teaching in order to see the status of academic discipline regularly as well as to explore the goals of learning where it has been, where it is currently and where it tends to be in the future.